2011
DOI: 10.1021/ie101805a
|View full text |Cite
|
Sign up to set email alerts
|

Modulating Electrochemical Activity in Polyaniline/Titanium Oxide Hybrid Nanostructured Ultrathin Films

Abstract: Hybrid and nanostructured ultrathin films of polyaniline (PANI) were fabricated using combined layer-by-layer (LbL) and surface sol−gel (SSG) processing with titanium oxide (TiO x ) layers. This enabled modulation of the electrochemical and the doping−dedoping process of the electroactive conjugated polymer with respect to thickness, presence of another polyelectrolyte, and intercalation of the inorganic slabs. The structure, composition, and viscoelastic behavior were proven by UV−vis absorbance, FT-IR, XPS, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 109 publications
0
9
0
Order By: Relevance
“…PIn can be effortlessly prepared either electrochemical or by synthetic oxidation of indole monomer (C 8 NH 7 ) with genuinely good thermal stability, high redox activity, moderate degradation rate, and better air stability in contrast with PAni and PPy 20 , 21 . Different literary works have been published uncovering the electrochemical properties of PIn, utilized in battery anodes, corrosion protection, nano light-emitting devices 7 , 22 – 24 etc. Among different nanometallics, nano-gold bunches have pulled in extensive consideration over the current years as a result of the predominant practical properties which is empowering them to be relevant in different fields extending from catalysis to electronic applications and sensors 25 28 .…”
Section: Introductionmentioning
confidence: 99%
“…PIn can be effortlessly prepared either electrochemical or by synthetic oxidation of indole monomer (C 8 NH 7 ) with genuinely good thermal stability, high redox activity, moderate degradation rate, and better air stability in contrast with PAni and PPy 20 , 21 . Different literary works have been published uncovering the electrochemical properties of PIn, utilized in battery anodes, corrosion protection, nano light-emitting devices 7 , 22 – 24 etc. Among different nanometallics, nano-gold bunches have pulled in extensive consideration over the current years as a result of the predominant practical properties which is empowering them to be relevant in different fields extending from catalysis to electronic applications and sensors 25 28 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it strongly interacts with acidic compounds through electrostatic interaction. So, the surface of NPs could be readily modified with monolayer dispersed positively charged PANI by a facile chemisorption approach . PANI is unique among the conjugated polymers since its doping level can be readily controlled through an acid‐doping/base‐undoping process.…”
Section: Resultsmentioning
confidence: 99%
“…(2) TiO 2 nanoparticles with their unique properties find their new and expanded application in this work. Recently, Advincula et al reported the fabrication of LBL films of polyaniline with titanium oxide formed by surface sol-gel process and the modulation of the electrochemical activity of the films [52]. Since the TiO 2 nanostructure formed by sol-gel method shows the pI value at 5.8 [53], it would also be possible to use this kind of TiO 2 to assemble LBL films with PAH on electrodes and realize the pH-switchable permeability of the films toward charged probes.…”
Section: Discussionmentioning
confidence: 99%